Phenotypic annotation of the mouse X chromosome - Cox, Brian J.; Vollmer, Marion; Tamplin, Owen; Lu, Mei; Biechele, Steffen; Gertsenstein, Marina; van Campenhout, Claude; Floss, Thomas; Kühn, Ralf; Wurst, Wolfgang; Lickert, Heiko; Rossant, Janet

(untitled) (Genome Research, 2010)
Mutational screens are an effective means used in the functional annotation of a genome. We present a method for a mutational screen of the mouse X chromosome using gene trap technologies. This method has the potential to screen all of the genes on the X chromosome without establishing mutant animals, as all gene-trapped embryonic stem (ES) cell lines are hemizygous null for mutations on the X chromosome. Based on this method, embryonic morphological phenotypes and expression patterns for 58 genes were assessed, ∼10% of all human and mouse syntenic genes on the X chromosome. Of these, 17 are novel embryonic lethal mutations and nine are mutant mouse models of genes associated with genetic disease in humans, including BCOR and PORCN. The rate of lethal mutations is similar to previous mutagenic screens of the autosomes. Interestingly, some genes associated with X-linked mental retardation (XLMR) in humans show lethal phenotypes in mice, suggesting that null mutations cannot be responsible for all cases of XLMR. The entire data set is available via the publicly accessible website (http://xlinkedgenes.ibme.utoronto.ca/).